Real‐time activation of central cholinergic circuits during recognition memory - Bonnì, Sonia; Ponzo, Viviana; Di Lorenzo, Francesco; Caltagirone, Carlo; Koch, Giacomo; Thut, Gregor (The European journal of neuroscience, 2017)
Short latency afferent inhibition (SAI) is a paired‐pulse transcranial magnetic stimulation (TMS) protocol that consists in the inhibition of the motor evoked potentials (MEPs) by afferent sensory impulses. SAI is thought to be mediated by cholinergic projections over M1 and can be considered a putative marker of central cholinergic activity. It is known that memory processes are regulated by acetylcholine. Nonetheless, the influence of memory tasks on SAI has not been investigated. Here we tested changes in SAI circuits in healthy subjects performing a computerized non‐verbal recognition memory task (RMT) requiring to recognize previously encoded faces. SAI protocol was recorded during five phases of the RMT: baseline, encoding, consolidation, retrieval, and post‐task. In the control task, subjects were asked to judge a visual feature of not previously presented faces. SAI protocol was applied over the same conditions as in the RMT. We found that SAI remarkably increases during the retrieval phase of the RMT as compared to baseline. On the other hand no change was observed during the control task. These findings show that SAI can be modulated by ongoing memory processes and support the hypothesis that SAI can be considered as a neurophysiological marker of central cholinergic activity. SAI can be modulated by ongoing recognition memory, specifically for retrieval process. SAI can be considered as a neurophysiological marker of central cholinergic activity. SAI protocol could be useful to study in vivo different forms of memory processes.